Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I'd like to find a closed form for $1^3+3^3+5^3+...+n^3$ where $n$ is an odd number.

How would I go about doing this?

I am aware that $1^3+2^3+3^3+4^3+...+n^3=\frac{n^2(n+1)^2}{4}$ but I'm not too sure how to proceed from here.

My gut feeling is telling me to multiply the above series by 8, then subtract it from the original, but it doesn't quite get me there because I'm going to have a whole lot of extra terms that I do not want.

share|improve this question

6 Answers 6

up vote 12 down vote accepted

By factorizing $2^3 = 8$ from the even terms, we can re-express the sum of the even terms:

$$2^3 + 4^3 + \dots + (n-1)^3 = 8\left(1^3 + 2^3 + \dots + \left(\frac{n-1}{2}\right)^3\right)$$

Simply subtract this from $1^3 + 2^3 + \dots + n^3$ to give the sum of the remaining odd terms. You can compute the formula for the RHS of the above equation using the equation you mentioned.

share|improve this answer

Using repeated differences we get $$ \begin{array}{llll} 1 & 28 & 153 & 496 & 1225 & 2556 & \\ 27 & 125 & 343 & 729 & 1331 & \\ 98 & 218 & 386 & 602 & \\ 120 & 168 & 216 & \\ 48 & 48 & \\ 0 & \\ \end{array} $$ Newton's interpolation formula then gives us $$ 1 \binom{n-1}{0} + 27 \binom{n-1}{1} + 98 \binom{n-1}{2} + 120 \binom{n-1}{3} + 48\binom{n-1}{4} = 2 n^4-n^2 $$

This is a technique well worth knowing. (The simplification was done with WA.)

share|improve this answer

If

$\color{blue}{n = 1}$, $\sum$ = 1

$\color{blue}{n=2}$, $\sum = 1^3 + 3^3 = 28 = 2^2 \cdot 7 = \color{blue}{2}^2(2\cdot \color{blue}{2}^2-1) $

$\color{blue}{n = 3}, \sum = 1^3 + 3^3 + 5^3 = 153 = 3^2 \cdot 17 = \color{blue}{3}^2(2\cdot \color{blue}{3}^2 - 1) $

$\color{blue}{n = 4}, \sum = 1^3 + 3^3 + 5^3 + 7^3 = 496 = 2^4\cdot 31 = \color{blue}{4}^2(2\cdot \color{blue}{4}^2 - 1)$

So, we can suppose that $$\sum_{k=1}^{n} (2k-1)^3 = n^2(2n^2 - 1)$$ This formula can be proved by method of mathematical induction.

share|improve this answer

It may be simpler to use a method that does not require any creativity:

Let n = (2k-1) here.

$\sum_{i=1}^k(2i-1)^3 = \sum_{i=1}^k(8i^3 - 12i^2 + 6i - 1) = 8\sum_{i=1}^ki^3 - 12\sum_{i=1}^ki^2 + 6\sum_{i=1}^ki - \sum_{i=1}^k1 = 8(\frac{k(k+1)}{2})^2 - 12\frac{k(k+1)(2k+1)}{6} + 6\frac{k(k+1)}{2} - k$

share|improve this answer
    
Be aware, though, that $\sum_{i=0}^k (2i+1)^3$ is the expression OP wants to find, not $\sum_{i=1}^k (2i+1)^3$. –  mathh Jun 26 at 12:08
    
Right, edited it. –  Wonder Jun 26 at 12:34

Note that $$\sum 1=n=C_n^1$$ $$\sum\sum1=\sum i=\frac{n(n+1)}{2}=C_{n+1}^2$$ $$\sum\sum\sum1=\sum\frac{i(i+1)}2=\frac{n(n+1)(n+2)}{2.3}=C_{n+2}^3$$$$\sum\sum\sum\sum1=\sum\frac{i(i+1)(i+2)}{2.3}=\frac{n(n+1)(n+2)(n+3)}{2.3.4}=C_{n+3}^4.$$

These are diagonals in Pascal's triangle.

From there, you derive $$\sum i^2=2\sum\frac{i(i+1)}2-\sum i=2C_{n+2}^3-C_{n+1}^2,$$ and $$\sum i^3=6\sum\frac{i(i+1)(i+2)}{6}-3\sum i^2-2\sum i=6C_{n+3}^4-6C_{n+2}^3+C_{n+1}^2.$$

share|improve this answer

Just for the collection:

From the identity $(2k-1)^3 = 2k^4-k^2 - 2(k-1)^4+(k-1)^2$, we see that if we denote $u_k = 2k^4-k^2$ then we have $(2k-1)^3=u_k - u_{k-1}$.

Thus, $$1^3+3^3+\cdots+(2n-1)^3 = \sum_{k=1}^n (2k-1)^3 = \sum_{k=1}^n (u_k - u_{k-1}) = u_n-u_0 = 2n^4-n^2.$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.